2017
DOI: 10.3390/ijgi6080236
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Characteristics of Twitter Users—Toward the Understanding of Geosocial Media Production

Abstract: Social media is a rich source of spatial data but it has also many flaws and well-known limitations, especially in regard to representation and representativeness, since very little is known about the demographics of the user population. At the same time, the use of locational services, is in fact, dependent on those characteristics. We address this gap in knowledge by exploring divides between Twitter users, based on the spatial and temporal distribution of the content they produce. We chose five cities and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…Based on the extraction results, we find that a large amount of Sina Weibo users posted very few geotagged social media data which is not enough for extracting their home location. Similar finding has also be proved by Rzeszewski et al [34].…”
Section: Home Location Extractionsupporting
confidence: 89%
See 2 more Smart Citations
“…Based on the extraction results, we find that a large amount of Sina Weibo users posted very few geotagged social media data which is not enough for extracting their home location. Similar finding has also be proved by Rzeszewski et al [34].…”
Section: Home Location Extractionsupporting
confidence: 89%
“…Last, the captures for different feasible locations were estimated, and the optimal location for a new retail agglomeration was determined. influence the final results of our study and can be considered as outliers [34]. Based on the study of Rzeszewski et al [34], we restricted geotagged microblogs to one location per user in our case.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, female users are reported low in agreeableness while using instant messaging more often than male users is high in agreeableness, whereas male users are reported low in openness while playing more online games compared to female users are high in openness. Rzeszewski and Beluch [100] addressed the gap (representation and representativeness) in data by investigating the LBSN users, based on the spatiotemporal distribution of the content produced (demographics of the user population). While Guan et al [101] studied the concentration and significance of users' thoughts on Sina Weibo and Feng et al [102] analyzed China's city network based on users' friend relationships and check-in behavior on Sina Weibo.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, long-distance movements were explored in [23]. Furthermore, clustering methods incorporating spatial, temporal, and textual information have been widely applied to infer activity types or travel purpose and segment user groups at an aggregated scale [30,31]. Results were generally verified with travel surveys or census data [9,32], and it was concluded that working and commercially related tweets or topics gave a better estimate.…”
Section: Related Work-mining Spatial Patterns From Geo-tweetsmentioning
confidence: 99%